Exploring the burden of the primary family caregivers of schizophrenia patients in Taiwan - Shu‐Ying Hou; Chiao‐Li Khale Ke; Yi‐Ching Su; For‐Wey Lung; Chun‐Jen Huang (2008)
The purpose of the present study was to investigate the burden of the primary family caregivers of schizophrenia patients and the factors that affect caregiver burden.A total of 126 pairs of patients and their primary family caregivers were recruited from the day care and acute wards of two teaching general hospitals. Demographic information was collected. All patients went through an interview with a senior psychiatrist using the Brief Psychiatric Rating Scale (BPRS). The Caregiver Burden Inventory-Brief Version and the Chinese Health Questionnaire (CHQ) were used to assess the caregiver burden and the caregivers' health condition. One-way analysis of variance and Pearson correlation were used to analyze the relationship between demographic factors and caregiver burden. Multiple regression was used to analyze predictors of burden of caregivers. Statistical significance in this study was defined as P <or= 0.05.The caregiver burden scores (25.9 +/- 10.7; range, 3-61) indicated a moderate burden level. Among the five dimensions of burden, caregiver anxiety (2.13 +/- 0.86) was the highest, followed by dependency of the patient (1.85 +/- 1.02), feeling shame and guilt (1.56 +/- 1.02), and family interference (1.43 +/- 0.83). The burden level of stigmata (1.32 +/- 1.24) was the lowest. The first three rankings of burden were 'I worry about his/her safety when he/she is alone' (2.26 +/- 1.15), 'I worry that she/he will become sick at any time' (2.23 +/- 1.10), and 'I feel he/she depends on me very much' (2.02 +/- 1.29). Patient satisfaction with medical staff support (P = 0.00), CHQ scores of the caregivers (P = 0.00), and the BPRS scores of the patients (P = 0.01) were significantly associated with the caregiver burden scores.The physical and mental health condition of the primary family caregiver of schizophrenia patients was the most important factor determining the caregiver burden level. Comprehensive multidisciplinary care of chronic schizophrenia patients is needed, care that supports the needs and improves the psychiatric symptoms of the patients, helps to decrease the caregiver burden level, and facilitates family participation in treatment.